A Comparison Between Two Definitions of Contrast-Associated Acute Kidney Injury for Long-Term Mortality in Elderly and Non-elderly Patients After Elective Percutaneous Coronary Intervention - He, Haoming; You, Zhebin; Lin, Xueqin; He, Chen; Zhang, Sicheng; Luo, Manqing; Lin, Maoqing; Zhang, Liwei; Lin, Kaiyang; Guo, Yansong (Frontiers in Cardiovascular Medicine, 2021)
Background: Contrast-associated acute kidney injury (CA-AKI) is responsible for a substantial proportion of the observed mortality that occurs after percutaneous coronary intervention (PCI), particularly in elderly patients. However, there has been significant and debate over whether the optimal definition of CA-AKI persists over prolonged periods due to variations in the prevalence and effects on prognosis. In this study, we aimed to identify whether different definitions of CA-AKI exert differential impacts on long-term mortality when compared between elderly and non-elderly patients receiving elective PCI. Methods: We prospectively investigated 5587 consenting patients undergoing elective PCI between January 2012 and December 2018. We considered two classical definitions of CA-AKI from the European Society of Urogenital Radiology (ESUR) and the Acute Kidney Injury Network (AKIN). Multivariable Cox regression analysis was used to investigate the association between CA-AKI and long-term mortality. We also performed interaction and stratified analyses according to age (≤75 or >75 years). Results: The incidence of CA-AKI according to the ESUR and AKIN definitions were 18.7% and 6.1%, respectively. After a median follow-up of 2.1 years, multivariable Cox regression analysis indicated that CA-AKI according to the AKIN definition was a risk factor for long-term mortality in the overall population (hazard ratio (HR)=2.20; 95% confidential interval (CI): 1.51-3.22; p<0.001); however, this was not the case for the ESUR definition (HR=1.27; 95% CI: 0.92-1.76; p=0.153). Further interaction analysis identified a signiﬁcant interaction between age and the ESUR definition (p=0.040). Stratified analyses also found an association between the ESUR definition and long-term mortality in patients >75 years-of-age (p=0.011), but not in patients ≤75 years-of-age (p=0.657). Conclusion: As a stringent definition of CA-AKI, the AKIN definition was significantly associated with long-term mortality in both non-elderly and elderly patients. However, in elderly patients, the more lenient definition provided by the ESUR was also significantly correlated with long-term mortality, which could sensitively identify high-risk elderly patients and may provide a better alternative.